Recovery of Rare Earth Elements and Yitrium from non-Magnetic Coal Fly Ash using Acetic Acid Solution - Hotden Manurung; Widya Rosita; I Made Bendiyasa; Agus Prasetya; Ferian Anggara; Widi Astuti; Dagus Resmana Djuanda; Himawan Tri Bayu Murti Petrus (Balai Besar Logam dan Mesin, 2020)
The increasing need of REY has been observed in industries such as catalyst industry, metallurgy, military, health and renewable energy resources. REY such as Ce, Nd, Y, and Eu has a prominent evidence to improve material properties such as high electropositive, good conductivity and renewable energy. Due to this increasing need of REY, exploration of alternative source has been conducted. One of the promising alternative sources is coal fly ash. The conventional method to recover REY from coal fly ash using inorganic acids is harmful to the environment. Thus, the exploration of REY extraction from coal fly ash using organic acid has been proposed in this study. The leaching agent was acetic acid applied for all operating condition. Regarding to the mineralization of REY in the form of siliceous minerals (non-magnetic coal fly ash). Silicate digestion was conducted using sodium hydroxide 8 M with solid-to-liquid of 25% to decompose the siliceous mineral. Further, the REY bound siliceous mineral will change to REY(OH)3. Temperature as one of the operating conditions was varied. The maximum recovery of leaching 20.58 %, 43.53 %, 17.38%, 40.96 %, 18.45 % and 32.74 % were achieved for Ce, Dy, La, Nd, Y and Yb respectively at temperature of 90 0C pH 1.74 and 120 minutes. For some metals, increasing the temperature higher than 70 0C does not provide any significant effect for REY recovery such as La and Ce.